Combined effects of internal exhaust gas recirculation and tumble motion generation in a flex-fuel direct injection engine. (1st August 2020) - Malaquias, Augusto César Teixeira; Netto, Nilton Antônio Diniz; da Costa, Roberto Berlini Rodrigues; Baêta, José Guilherme Coelho
Highlights: Internal EGR and tumble flow reduced the exhaust emissions of CO, HC, CO2 and NOX . Combined techniques led to fuel conversion efficiency gains of up to 3.5%. E100 was the most suitable fuel in the tests on a single-cylinder flex-fuel engine. In-cylinder tumble motion restored combustion phasing lost in the iEGR-only tests. Abstract: The increasing demands placed on the global automotive industry for reducing the environmental impact of its activities have stimulated changes in the concept and design of internal combustion engines. Seeking to comply with a more sustainable future of mobility, the purpose of the present work is to study the impacts of exhaust gas recirculation, combined with changes in the in-cylinder primary flow structure, in the experimental operation of a single-cylinder research engine. The two main fuels for the Brazilian light-vehicle fleet, gasohol (E27) and bioethanol derived from sugarcane (E100), were directly injected in the tests. After performing a baseline calibration to investigate the best valve timing setup for the camshaft in order to optimize the trapped EGR, the induced tumble motion proved to be an effective method to speed up the combustion flame propagation, enhancing the fuel conversion efficiency. The results showed up to 10% fuel consumption reduction, lower exhaust pollutant emissions of CO2, CO, NOX and HC when compared to the baseline engine experiments. Improvements in combustion phasing were observed, with the CoV of IMEP always remaining below the upper limit of 3.5%. The internal EGR combination with in-cylinder tumble flow was a powerful strategy to enhance the overall engine efficiency whilst minimizing its environmental impact, especially for the ethanol-fueled tests, in which the compression ratio was raised from 11.5 to 15.0.